Developments of cartography and geodesy in Albania (contribution of Prof. Spiro Boçi in practical Albanian geodesy and cartography) - Nikolli, Pal; Idrizi, Bashkim; Kabashi, Ismail (Geodesy and Cartography, 2021)
Name of Prof. Dr Spiro Boçi is known in the Albanian academic and scientific world, both inside and outside Albania, for his valuable contributions in the field of cartography, especially practical cartography and geodesy. With the experience of a passionate researcher, prof. Spiro Boçi has left a mark on Albanian scientific thought. He has a balance of over 40 years of extensive and successful research, publishing and pedagogical activity.The legacy of prof. Spiros is diverse and reflects his broad interests. Scientific and pedagogical work of prof. Spiros will serve today’s and tomorrow’s generations and be a guide for them. Even today, Prof. Spiro Boçi continues to write and contribute successfully to the development of the science of cartography and geodesy.In this paper an attempt is made to analyze the activity of Prof. Spiro Boçi in the field of practical cartography and geodesy and especially in the application of cartographic and geodetic methods in studying the movement of the Albanian Adriatic coastline.